Somatosympathetic Vasoconstrictor Reflexes in Human Spinal Cord Injury: Responses to Innocuous and Noxious Sensory Stimulation below Lesion - Macefield, Vaughan G.; Burton, Alexander R.; Brown, Rachael A. (Frontiers in Physiology, 2012)
It is known that the sudden increases in blood pressure associated with autonomic dysreflexia in people with spinal cord injury (SCI) is due to a spinally-mediated reflex activation of sympathetic vasoconstrictor neurones supplying skeletal muscle and the gut. Apart from visceral inputs, such as those originating from a distended bladder, there is a prevailing opinion that autonomic dysreflexia can be triggered by noxious stimulation below the lesion. However, do noxious inputs really cause an increase in blood pressure in SCI? Using microelectrodes inserted into a peripheral nerve to record sympathetic nerve activity we had previously shown that selective stimulation of small-diameter afferents in muscle or skin, induced by bolus injection of hypertonic saline into the tibialis anterior muscle or the overlying skin, evokes a sustained increase in muscle sympathetic nerve activity and blood pressure and a transient increase in skin sympathetic nerve activity and decrease in skin blood flow. We postulated that these sympathetic responses would be exaggerated in SCI, with a purely noxious stimulus causing long-lasting increases in blood pressure and long-lasting decreases in skin blood flow. Surprisingly, though, we found that intramuscular or subcutaneous injection of hypertonic saline into the leg caused negligible changes in these parameters. Conversely, weak electrical stimulation over the abdominal wall, which in able-bodied subjects is not painful and activates large-diameter cutaneous afferents, caused a marked increase in blood pressure in SCI but not in able-bodied subjects. This suggests that it is activation of large-diameter somatic afferents, not small-diameter afferents, that triggers increases in sympathetic outflow in SCI. Whether the responses to activation of large-diameter afferents reflect plastic changes in the spinal cord in SCI is unknown.